2016
DOI: 10.7554/elife.14814
|View full text |Cite
|
Sign up to set email alerts
|

Golgi self-correction generates bioequivalent glycans to preserve cellular homeostasis

Abstract: Essential biological systems employ self-correcting mechanisms to maintain cellular homeostasis. Mammalian cell function is dynamically regulated by the interaction of cell surface galectins with branched N-glycans. Here we report that N-glycan branching deficiency triggers the Golgi to generate bioequivalent N-glycans that preserve galectin-glycoprotein interactions and cellular homeostasis. Galectins bind N-acetyllactosamine (LacNAc) units within N-glycans initiated from UDP-GlcNAc by the medial-Golgi branch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
71
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 55 publications
(83 reference statements)
4
71
0
Order By: Relevance
“…However, GlcNAc or kifunensine did not acutely alter the metabolic state of the T cell, as measured by the oxygen consumption rate and extracellular acidification rate. Consistent with this, we have previously shown that lowering branching does not alter UDP-GlcNAc levels in T cells (Mkhikian et al, 2016). GlcNAc does raise UDP-GlcNAc levels, which may impact other glycan pathways such as O-glycans, O-GlcNAc or CMP-sialic scid, in addition to N-glycan branching.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, GlcNAc or kifunensine did not acutely alter the metabolic state of the T cell, as measured by the oxygen consumption rate and extracellular acidification rate. Consistent with this, we have previously shown that lowering branching does not alter UDP-GlcNAc levels in T cells (Mkhikian et al, 2016). GlcNAc does raise UDP-GlcNAc levels, which may impact other glycan pathways such as O-glycans, O-GlcNAc or CMP-sialic scid, in addition to N-glycan branching.…”
Section: Discussionsupporting
confidence: 85%
“…Branching in N-glycans depends on UDP-GlcNAc biosynthesis via the hexosamine pathway (Dennis et al, 2009; Grigorian et al, 2011, 2007; Lau et al, 2007; Mkhikian et al, 2016). De novo synthesis of UDP-GlcNAc, the sugar-nucleotide donor substrate required by the N-glycan branching Golgi enzymes Mgat1, 2, 4 and 5, begins with the conversion of fructose-6-phosphate to glucosamine-6-phosphate by the rate-limiting enzyme glutamine-fructose-6-phosphate transaminase (GFPT, Figure 1A).…”
Section: Introductionmentioning
confidence: 99%
“…All in all, the ultimate question persists: “If glycans are so important for immunity, why is immunological involvement not more common within CDG?”. A few light‐shedding assumptions can be advanced: Since total glycosylation abrogation is incompatible with life, patients still retain residual levels of glycosylating capacity, which may prevent the development of more severe phenotypes, preserving reasonable immune responses; The possible development of bioequivalence glycosylation mechanisms which create alternative pathways, allowing to achieve similar functionality; The differential enzymatic expression and existence of cell/tissue/organ specific defects which leads to site‐specific anomalies, thus restricting systemic and more severe phenotypes …”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this observation represents the rst report that the anticancer effect of metformin is related to UDP-GlcNAc. As is known, UDP-GlcNAc is a common donor substrate for the N-glycosylation of most cell-surface receptors and transporters in eukaryotes [45]. Previous works indicated that glycoproteins with few N-glycans were signi cantly increased in a switchlike response to the enhanced UDP-GlcNAc level, such as TβR, CTLA-4 and GLUT4 which mediated organogenesis, differentiation and cell cycle arrest [46,47].…”
Section: Discussionmentioning
confidence: 99%